Raising juveniles - Bell, Clive; Gersbach, Hans; Schneider, Maik T. (Games and economic behavior, 2012)
This paper investigates how families decide how juveniles use their time. The problem is analyzed in three variations: (i) a 'decentralized' scheme, in which parents control the main budget, but their children dispose of their time as they see fit, together with any earnings from work on their own account; (ii) 'hierarchy', in which parents can enforce, at some cost, particular levels of schooling and supervised work contributing to the main budget; and (iii) the cooperative solution, in which resources are pooled and the threat point is one of the non-cooperative outcomes. Adults choose which game is played. While the subgame perfect equilibrium of the overall game is pareto-efficient, it may yield less education than 'hierarchy'. Restrictions on child labor and compulsory schooling generally affect both the threat point and the feasible set of bargaining outcomes. Families may choose more schooling than the legal minimum.